(untitled) (Journal of Analytical Oncology, 2013)
Purpose: This pharmacokinetic study was designed to investigate whether the co-administration of the monoclonal antibody bevacizumab (BVC) shows potential to modulate the plasma disposition of irinotecan (CPT-11) and its metabolites. Patients and Methods: Ten patients suffering from advanced colorectal cancer entered this pharmacokinetic study. Patients received CPT-11 as a 60 min i.v. - infusion (180 mg/m2, total dose 339 ± 32 mg) weekly for six weeks. BVC was administered biweekly as an intravenous 90 min infusion containing 5 mg BVC per kg body weight in 100 ml balanced sodium chloride solution. Pre-medication consisted of tropisetrone (3 mg i.v. push) and atropine (0.5 mg i.v.) one hour before CPT-11 infusion. Plasma samples were analysed during / after the first (MONO) and after the third CPT-11 infusion (BVC regimen). Results: BVC did not alter plasma disposition and pharmacokinetics of the parent compound CPT-11, but in contrary BVC appeared to lower the plasma concentrations of the metabolites SN-38, SN-38gluc and APC. Conclusion: Overall, our findings indicate that administration of BVC prior to chemotherapy showed no clinically significant impact on the pharmacokinetics and metabolic activation of CPT-11.